Biocomposites Recent Advances - Elnashar, Magdy M.M; Karakuş, Selcan (IntechOpen, 2023)
This book discusses the synthesis, characterization and applications of biocomposites and nano-biocomposites. It focuses on recent studies, applications, and new technological developments in the fundamental properties of biocomposites. The book includes six chapters that address topics such as the biomedical applications and characterization of biopolymers, biocomposites, and nano-biocomposites.